PENGGUNAAN MEDIA SOSIAL SEBAGAI ALAT BANTU PROMOSI TERHADAP PENINGKATAN KINERJA BISNIS PADA UMKM ( STUDI KASUS UMKM KABUPATEN BUTON SELATAN) - Sueni Jultianti Mardin; Ramly; Muhammad Khaedar Sahib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to find out the influence of social media on the improvement of business performance in MSMEs in South Buton Regency. The population used in this study is MSMEs who use Facebook as a promotion tool and the sample used for this study is 92 Respondents. This research uses the Quantitative Method with a Regression Analysis approach. Data is collected through the distribution of questionnaires, this data is tested through several stages such as descriptive test, data validity test, data reliability test, normality test, heteroscredasticity test, simple liner regression test, hypothesis test (t test), R2 determination test with the help of SPSS (Statistical Package For The Social Science) version 25. In this research, the use of social media has a positive and significant effect on business performance. This shows that their chances are greater to see an improvement in business performance, both in terms of increased sales, brand awareness, and long-term market growth.